2023
DOI: 10.1186/s13018-023-03550-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram to predict the risk of surgical site infection within 1 month after transforaminal lumbar interbody fusion

Abstract: Objective Surgical site infection (SSI), a common serious complication within 1 month after transforaminal lumbar interbody fusion (TLIF), usually leads to poor prognosis and even death. The objective of this study is to investigate the factors related to SSI within 1 month after TLIF. We have developed a dynamic nomogram to change treatment or prevent infection based on accurate predictions. Materials and methods We retrospectively analyzed 383 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study findings revealed that the incidence of postoperative SSI in elderly patients undergoing open lumbar spine surgery was 2.94%, which agreed with the results reported by Le et al 11 It was of great significance for clinical practice to predict early onset of SSI in preoperation. 12 , 13 , 14 Therefore, we developed and validated a novel nomogram model for preoperative prediction of postoperative SSI risk in elderly patients who undergone open lumbar spine surgery. Our study identified three predictive factors, namely obesity, hypoalbuminemia and drinking history.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings revealed that the incidence of postoperative SSI in elderly patients undergoing open lumbar spine surgery was 2.94%, which agreed with the results reported by Le et al 11 It was of great significance for clinical practice to predict early onset of SSI in preoperation. 12 , 13 , 14 Therefore, we developed and validated a novel nomogram model for preoperative prediction of postoperative SSI risk in elderly patients who undergone open lumbar spine surgery. Our study identified three predictive factors, namely obesity, hypoalbuminemia and drinking history.…”
Section: Discussionmentioning
confidence: 99%